Challenges in Managing Corneal Ulcer with Hypopyon in an Uncontrolled Diabetes Mellitus Patient: A Case Report - Nyoman Yuni Suryani Dharmaputri P.; Luh Putu Eka Naryati (HM Publisher, 2025)
Background: Corneal ulcer is an ophthalmological emergency that can cause blindness. The risk of increasing this complication occurs mainly in patients with systemic diseases such as diabetes mellitus. Case presentation: a 50-year-old male patient was treated with OS corneal ulcer cum hypopyon with a history of diabetes mellitus. On the first visit, the visual acuity examination was found to be 6/7.5 in both eyes, and the results of the corneal erosion examination were in the left eye. However, on further evaluation, the left eye's visual acuity worsened to 6/45. Anterior segment examination of the left eye showed infiltration and hypopyon formation on the next visit evaluation. The patient's condition did not improve with conventional therapy, so surgical intervention was performed in the form of amniotic membrane transplantation, hypopyon aspiration, and intracameral antibiotic injection. Corneal and hypopyon scraping culture results did not show bacterial and fungal growth. Corneal condition improved after blood sugar was controlled with insulin. Conclusion: Corneal ulcers with hypopyon in patients with diabetes and diabetic keratopathy require a comprehensive approach to address infection, inflammation, and impaired healing. Multidisciplinary collaboration, especially blood sugar control, is important to improve long-term prognosis.